The effects of Orem's self-care theory on self-care behaviors among older women with hypertension: A randomized controlled trial - Shahrbanoo Nasresabetghadam; Mehri Jahanshahi; Zahra Fotokian; Mahboobeh Nasiri; Mahmoud Hajiahmadi (Kashan University of Medical Sciences, 2021)
Background: Lifestyle modification and self-care have potential effects on hypertension management among older women. Objectives: The aim of this study was to assess the effects of using Orem's Self-Care Deficit (OSCD) theory on self-care behaviors among older women with hypertension. Methods: This clinical trial was conducted in 2018-2019. A 70-year-old woman with hypertension were conveniently recruited from healthcare centers in Ramsar, Iran, and randomly allocated to a control and an intervention group. Participants in the intervention group received self-care education based on the OSCD theory. The control group received no intervention. Data were collected using a personal characteristics questionnaire, a researcher-made self-care need assessment checklist, and the Hypertension Self-Care Activity Level Effects questionnaire. The Wilcoxon and the Mann-Whitney U-tests were used to analyze the data. Results: There were no significant differences between the groups respecting the pretest mean scores of medication adherence, weight control, physical activity, and nutrition-related self-care behaviors (P > 0.05). However, after the intervention, the between-group difference respecting the mean scores of these behaviors were statistically significant (P < 0.001). Conclusion: The OSCD theory is effective in promoting self-care behaviors among women with hypertension. Therefore, its use is recommended to improve hypertension management and quality of life and reduce treatment-related costs in these patients.